Human Capital, Training Pathways and Educational and Professional Guidance in China (Sinología hispánica. China Studies Review, 2019)
One of the Government's priorities is to swap from an industrial economy and low salaries to one of Services and high salaries. For this, the government needs to increase the quality of Human Capital, understood as the increase in the average educational level of the population. An educational measure to achieve this goal is to enhance educational and vocational guidance. Orientation is conceived as a measure designed to optimize the adjustment between the education system and labor market. Although it is a measure present in the Chinese educational system before, it is not until 2012, when the government is committed to a model of Educational andProfessional Guidance focused on the developmentof the individual's career. The objective of thispaper is to analyze how educational transitionsare from one educational stage to another, andfrom one educational level to another, to knowthe problems and factors associated with droppedfrom school. Once detected the different typesof transition in the Chinese education system.We contrast it with the theoretical model ofeducational and professional guidance focusedon the development of the individual's vocationalcareer. At the methodological level, a review ofthe research and of the databases to be usedis carried out. Finally, the results show howdifferent itinerary models that Chinese studentstake according to their socio-educational profiledo not fit with the theoretical model of CareerEducation.